Lying and social norms: A lab-in-the-field experiment with children - Despoina Alempaki; Genyue Fu; Jingcheng Fu (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2021)
We conduct a lab-in-the-field experiment with 567 children, aged four to eleven, in which we investigate the effect of social norms on lying and test whether norm sensitivity changes with age. Children think about a number between 1 and 6 in private, then roll a die, and report whether the number that came up is the same as the one they thought of. Just before making their report, we expose children to different empirical and normative information prescribing lying or honesty. We show that a normative intervention suggesting other children approve of honesty effectively reduces lying. We find limited evidence of the influence of our empirical interventions: information suggesting other children report honestly is effective only for younger children, while information suggesting other children report dishonestly does not influence lying patterns. We further observe that, although lying is omnipresent across all age groups, honesty significantly increases with age.
Keywords: C9; D8; 330; truth-telling; lying; social norms; children; lab-in-the-field experiment